Antibody‐ and TRIM21‐dependent intracellular restriction of Salmonella enterica. Issue 2 (27th June 2014) - Rakebrandt, Nikolas; Lentes, Sabine; Neumann, Heinz; James, Leo C.; Neumann‐Staubitz, Petra
Abstract TRIM21 ('tripartite motif‐containing protein 21', Ro52) is a ubiquitously expressed cytosolic Fc receptor, which has a potent role in protective immunity against nonenveloped viruses. TRIM21 mediates intracellular neutralisation of antibody‐coated viruses, a process called ADIN (antibody‐dependent intracellular neutralisation). Our results reveal a similar mechanism to fight bacterial infections. TRIM21 is recruited to the intracellular pathogen Salmonella enterica in epithelial cells early in infection. TRIM21 does not bind directly to S. enterica, but to antibodies opsonising it. Most importantly, bacterial restriction is dependent on TRIM21 as well as on the opsonisation state of the bacteria. Finally, Salmonella and TRIM21 colocalise with the autophagosomal marker LC3, and intracellular defence is enhanced in starved cells suggesting an involvement of the autophagocytic pathway. Our data extend the protective role of TRIM21 from viruses to bacteria and thereby strengthening the general role of ADIN in cellular immunity.